Concerns on table top size in a fast food restaurant among selected dine-in customers - Sison, Mira Angela S. (UP College of Home Economics, 2011)
The study aimed to determine the concerns of selected dine-in fast food customers in relation to table top size and the probable causes of these concerns. This is an explanatory study that used quantitative and qualitative research paradigms. The data collection methods employed in the study were survey, direct observation and documentation. The instruments included a survey questionnaire, an observation sheet, a camera, a pen, and paper. Purposive sampling was employed in selecting the 32 dine-in customers who participated in the study. Data collected from the survey and direct observation was then tabulated, ranked by frequency and analyzed. Results showed that 22 of the 32 respondents did not have any concerns with the table top size. This indicates that the 700 mm by 700 mm table top size was adequate for the needs of most respondents. Ten respondents had concerns with the table top size but only eight respondents gave valid answers: the other two were deemed questionable. Among the frequent and valid concerns include the table being too narrow, respondents' elbows bumping their companion, the overall table top size being too small, and crowding of food items on one side of the table top. The most probable causes for these concerns were the seating arrangement and the presence of children who play while eating. Height, posture, and the amount of food ordered were not found to be significant causes for these concerns. The results of this study also showed that design standards are not isolated and absolute solutions in all situations. Design standards are templates and recommendations that must be applied while taking other factors into consideration.